Hubungan Peran Petugas Kesehatan Dengan Pencegahan Demam Berdarah Dengue Di Gampong Seupeu Kecamatan Kuta Baro Aceh Besar - Yadi Putra; Urip Pratama; Ulfa Adrikal Muna (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Efforts to prevent dengue fever by controlling the transmission of dengue fever virus by eradicating dengue mosquito vectors with the implementation of 3 M where the role of health workers is very important in this case. The purpose of this study was to determine the relationship between the role of health workers and Dengue Fever Prevention in Gampong Seupeu, Kuta Baro District, Aceh Besar Regency. This research method uses an analytic design with a cross sectional approach with a population of 256 family heads (KK) and a sample size of 72 family heads (KK), the sampling technique is stratified random sampling. Data collection using a questionnaire. This study was conducted on July 6-17, 2023 with univariate and bivariate analysis using the chi-square test. The results showed that of the 72 respondents most of the prevention efforts against dengue hemorrhagic fever in the category, the role of health workers was less as many as 42 people (58.3%) and played as many as 30 people (41.7%). the role of health workers (p=0.007) with efforts to prevent dengue hemorrhagic fever. Conclusion there is a role of health workers with efforts to prevent dengue hemorrhagic fever. It is recommended at the research site to hold health counseling about dengue hemorrhagic fever, so that people can know about dengue hemorrhagic fever and how to prevent dengue hemorrhagic fever.